2011
DOI: 10.3109/09637486.2010.537254
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compositions and glycemic responses to banana varieties

Abstract: Chemical compositions and glycemic indices of four varieties of banana (Musa spp.) (kolikuttu-Silk AAB, embul-Mysore AAB, anamalu-Gros Michel AAA, seeni kesel-Pisang Awak ABB) were determined. Silk, Gros Michel, Pisang Awak and Mysore contained the highest percentages of starch (14%), sucrose (38%), free glucose (29%) and fructose (58%) as a percentage of the total available carbohydrate content respectively. Total dietary fiber contents of four varieties ranged from 2.7 to 5.3%. Glycemic indices of Silk, Myso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
2
18
0
5
Order By: Relevance
“…The literature has highlighted the effect of fibers on the glycemic response, especially soluble fibers (Hettiaratchi et al, 2011;Menezes et al, 2009;Mira et al, 2009). Among the fruits mentioned, the fiber isolated from passion fruit has been identified as having hypoglycemic effects (Salgado et al, 2010, Zeraik et al, 2010, which was also observed in the present study, where the GI of this fruit was one of the lowest among those evaluated.…”
Section: Discussionsupporting
confidence: 70%
“…The literature has highlighted the effect of fibers on the glycemic response, especially soluble fibers (Hettiaratchi et al, 2011;Menezes et al, 2009;Mira et al, 2009). Among the fruits mentioned, the fiber isolated from passion fruit has been identified as having hypoglycemic effects (Salgado et al, 2010, Zeraik et al, 2010, which was also observed in the present study, where the GI of this fruit was one of the lowest among those evaluated.…”
Section: Discussionsupporting
confidence: 70%
“…SK was comprised of the highest total carbohydrate content followed in decreasing order by PU, KK, RT and AK (p<0.05). The values obtained from this study in comparison to those available in literature showed somewhat higher values for ash contents, fairly lower values for crude fat a contents and similar values for moisture and total carbohydrate contents with that reported by Hettiaratchi et al (2011) who analyzed Kolikuttu, Seeni kesel and Embul kesel varieties. Deraniyagala et al (1994) determined total carbohydrate contents of Kolikuttu, Anamalu and Embul kesel varieties resulting somewhat higher values than the present study.…”
Section: Resultssupporting
confidence: 83%
“…The sugar sources that provide at least a 1:1 ratio glucose/fructose are unlikely to produce symptoms of gastrointestinal distress, such as cramping and diarrhea (Barrett & Gibson, 2007). In addition, the banana shows a low glycemic index (Hettiaratchi, Ekanayake, & Welihinda, 2011) and low production of cumulative gas on in vitro intestinal microbial fermentation (Low, Williams, D'arcy, Flanagan, & Gidley, 2015). Therefore, people who suffer from intestinal disorders or type II diabetes can consume banana.…”
Section: Mono-and Disaccharides Content In the Ripe Banana Pulp Andmentioning
confidence: 99%
“…Recent studies also showed that banana has remarkable amounts of oligosaccharides, especially fructans type FOS (fructooligosaccharides) and short‐chain inulins, such as 1‐kestose (1‐kestotriose, GF 2 ), 1,1‐nystose (Der Agopian, Soares, Purgatto, Cordenunsi, & Lajolo, ), 6‐kestotriose, 6G‐kestotriose (older name, neokestose), bifurcose (1,6‐kestotetraose), inulobiose (F 2 ), and inulotriose (F 3 ) (Cruz‐Cárdenas et al, ; Der Agopian, Purgatto, Cordenunsi, & Lajolo, ). In addition, the banana shows low glycemic index (Hettiaratchi, Ekanayake, & Welihinda, ), positive effect on the fecal microbiota of healthy adult women when consumed daily (Mitsou et al, ) and contribute to maintain a good performance when consumed before or during physical exercise (Nieman et al, ).…”
Section: Introductionmentioning
confidence: 99%